Pengaruh Kualitas Pelayanan, Promosi, Dan Harga Terhadap Kepuasan Konsumen Ai-Cha Palembang - Nicholas Kusuma; Idham Cholid (MDP Student Conference, 2026)
This study aims to analyze the effect of service quality, promotion, and price on consumer satisfaction. The research employed a quantitative approach using a survey method. The population consisted of consumers, with a sample of 384 The results indicate that service quality, promotion, and price each have a positive and significant effect on consumer satisfaction. Simultaneously, the three independent variables significantly influence consumer satisfaction. The coefficient of determination shows that service quality, promotion, and price explain 11.5% of the variation in consumer satisfaction, while the remaining percentage is influenced by other factors not examined in this study. These findings suggest that improving service quality, implementing effective promotional strategies, and setting appropriate prices can enhance consumer satisfaction.